Current Perspectives in Teaching English for Specific Purposes - Garcia Laborda, Jesus; Litzler, Mary Frances (Onomázein, 2015)
Interest in Languages for Specific Purposes (LSP) courses has grown in recent years (Harding, 2007). For this reason a paper on the current situation in the field is of relevance. The present article provides a discussion of English for Specific Purposes and it does so by reviewing the history and background of this area of teaching, proposing a definition, and describing issues affecting it today, such as course design and needs analysis, context, student and teacher characteristics, materials, and expected directions for the future.